Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1530/eje-08-0325
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones in children with epilepsy during long-term administration of carbamazepine and valproate

Abstract: Objective: This study evaluates the effects of long-term carbamazepine (CBZ) and valproate acid (VPA) therapy on thyroid function in epileptic children. Design: A prospective study performed in 32 newly diagnosed pediatric patients, subdivided into two groups: 18 patients treated with CBZ and 14 patients treated with VPA. Thirty-two sex-and agematched subjects served as controls. Methods: Serum TSH, thyroxine (T 4 ), triiodothyronine (T 3 ), free thyroxine (fT 4 ), free triiodothyronine (fT 3 ), thyroid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
55
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 41 publications
13
55
4
Order By: Relevance
“…In this cohort, it has been shown that TH profiles in subjects without anti-epileptic drugs (AEDs) were comparable with the general population. However, AEDs were strongly associated with decreased T 4 , free T 4 (FT 4 ), T 3 , and rT 3 levels which is in agreement with other studies (24,25,26). It has been speculated that the changed thyroid parameters in patients that use AEDs can be explained by an influence of AEDs on binding proteins (27), a stimulation of hepatic degradation or conjugation of TH (28) or an altered peripheral deiodinase activity (23).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this cohort, it has been shown that TH profiles in subjects without anti-epileptic drugs (AEDs) were comparable with the general population. However, AEDs were strongly associated with decreased T 4 , free T 4 (FT 4 ), T 3 , and rT 3 levels which is in agreement with other studies (24,25,26). It has been speculated that the changed thyroid parameters in patients that use AEDs can be explained by an influence of AEDs on binding proteins (27), a stimulation of hepatic degradation or conjugation of TH (28) or an altered peripheral deiodinase activity (23).…”
Section: Introductionsupporting
confidence: 87%
“…Due to the observational nature of this study, it is very difficult to draw any conclusions on the causative or mechanistic features of these results. It is very well possible, although speculative, that AEDs interfere with the transport, metabolism, or excretion of trace elements, as is described for TH (23,24,25,26,27,28). Furthermore, although the generalizability of our findings may be limited, it is important to be aware of confounders if Se or Cu levels are analyzed in subjects on commonly prescribed AEDs.…”
Section: Figurementioning
confidence: 84%
“…Notably, T 3 was not comparably affected by UGT-inducing agents in these studies, a finding which has been attributed to primary metabolism of T 3 through sulfation and deiodination rather than glucuronidation in humans, in contrast with rats (Benedetti et al 2005;Findlay et al 2000;Visser et al 1993). More significantly, no notable increase in TSH was reported in most of these clinical studies (Apeland et al 2006;Benedetti et al 2005;Isojärvi et al 2001;Verrotti et al 2009). Because of this lack of TSH change or clinical thyroid illness, the collective human literature suggests that little to no effect on thyroid function occurs in otherwise healthy subjects given DME-inducing agents.…”
Section: Endogenous Thyroid Hormone Effects Associated With Prototypimentioning
confidence: 77%
“…11,12 Though there have been studies suggesting that carbamazepine-induced reduction in thyroid hormone levels is not associated with clinical hypothyroidism, there have been studies suggesting the contrary. 13,14 Reports on the effect of VPA on the thyroid hormones balance are conflicting, and both low and unchanged serum thyroxine (T4) and free thyroxine (T4) levels have been found in patients receiving VPA monotherapy, never associated with overt thyroid dysfunction. 11,15 A comparative studies correlating abnormalities of thyroid function tests and clinical thyroid status of patients on monotherapy with the frontline antiepileptic drugs, namely phenytoin, valproate and carbamazepine are lacking, especially in the Indian set-up.…”
Section: Introductionmentioning
confidence: 99%